Peningkatan Kesejahteraan Barefoot Entrepreneurs Melalui Pemanfaatan Limbah Pasar Di “Pasar Semangat Dalam” - Hastin Umi Anisah; Meiske Claudia; Wimby Wandary; Raden Roro Yulianti; Marijati Sangen (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2021)
This service activity aims to empower MSMEs, traders associations in the “Semangat Dalam” Market (barefoot entrepreneurs) so that in the end they can improve their welfare. The approach method to achieve the goals of the service activities carried out is to provide counseling to the target audience - through the delivery of discourse to open insights or bring up new ideas in their entrepreneurial activities. The target audience is a handful of market traders located at Jalan Semangat Dalam, Hadil Bhakti. The result of this service activity is the opening of the target audience's insight so that they are willing and able to make more efforts in utilizing market waste that has the potential to increase the variety of trade products, and to be more introspective not to get involved with debt, especially from loan sharks in an effort to increase the variety of their trading products. Keywords: barefoot entrepreneurs, MSME’s, market waste utilization